Analytical Solution for Consolidation of Vertical Drains-Impervious Piles with Multiple Composite Foundations under Nonuniform Initial Pore Pressure and Time-Dependent Well Resistance. (11th May 2022) - Zhang, Yuguo; Zhao, Yamin
Abstract : For the vertical drains-impervious pile multiple composite foundation consolidation problem, the effects of nonuniform distribution of initial pore pressure, variation of well resistance with time, and combined radial and vertical seepage in the soil are considered, and a consolidation control equation based on the assumption of equal strain is established based on the axisymmetric model. The analytical solution method is used to give an analytical solution for the consolidation of multiple composite foundations with vertical drains-impervious piles with trapezoidal, rectangular, positive triangle, and inverted triangular distribution of initial pore pressure. The reasonableness of the solution of this study is verified by degradation analysis. According to the solution of the study, the consolidation properties of the multicomposite foundation were analyzed. The results show that the initial pore pressure is faster to consolidate with trapezoidal distribution than with rectangular distribution, the slowest to consolidate with positive triangular distribution, and the fastest to consolidate with inverted triangular distribution, and the larger the initial pore pressure value at the base of the soil layer, the slower the consolidation; the consolidation rate of the foundation all decreases with the increase of the well resistance factor, and the change of the well resistance mainly has an important influence on the later consolidation of the foundation; the vertical permeability coefficient of the soil has a greater influence on the consolidation of the foundation at the initial stage when the foundation thickness is small, and the vertical permeability coefficient of the soil has greater influence on the consolidation of the foundation at the later stage when the foundation thickness is large; the consolidation rate of foundation increases with the increase of replacement rate of impervious pile, compression modulus, and vertical permeability coefficient of soil. Compared with the single pile foundation, the multicomposite foundation can significantly improve the consolidation rate of foundation.